Erdős-Ko-Rado theorems for set partitions with certain block size - Ku, Cheng Yeaw (2021)
In this paper, we prove Erdős-Ko-Rado type results for (a) family of set partitions where the size of each block is a multiple of k; and (b) family of set partitions with minimum block size k.